A structural analysis of disappointment aversion in a real effort competition - Prowse, V; Gill, D (University of Oxford, 2009)
We develop a novel computerized real effort task, based on moving sliders across a screen, to test experimentally whether agents are disappointment averse when they compete in a real effort sequential-move tournament. Our theory predicts that a disappointment averse agent, who is loss averse around her endogenous expectations-based reference point, responds negatively to her rival's effort. We find significant evidence for this discouragement effect, and use the Method of Simulated Moments to estimate the strength of disappointment aversion on average and the heterogeneity in disappointment aversion across the population.